2014
DOI: 10.1158/0008-5472.can-13-3065
|View full text |Cite
|
Sign up to set email alerts
|

Transient Ablation of Regulatory T cells Improves Antitumor Immunity in Colitis-Associated Colon Cancer

Abstract: Regulatory T cells (Treg) are supportive to cancer development in most tissues, but their role in colitisassociated colon cancer (CAC) remains unclear. In this study, we investigated the role of CD4

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(103 citation statements)
references
References 46 publications
6
97
0
Order By: Relevance
“…To assess whether hypoxia is induced during CAC and whether low oxygen levels may impair an anti-tumour response, BALB/c mice were subjected to the azoxymethane (AOM)/dextran sulfate sodium (DSS) regimen, a well-established protocol for the induction of CAC [14, 16]. After injection of the procarcinogen AOM, the repeated administration of DSS via the drinking water induces a strong inflammatory response in the intestine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess whether hypoxia is induced during CAC and whether low oxygen levels may impair an anti-tumour response, BALB/c mice were subjected to the azoxymethane (AOM)/dextran sulfate sodium (DSS) regimen, a well-established protocol for the induction of CAC [14, 16]. After injection of the procarcinogen AOM, the repeated administration of DSS via the drinking water induces a strong inflammatory response in the intestine.…”
Section: Resultsmentioning
confidence: 99%
“…After injection of the procarcinogen AOM, the repeated administration of DSS via the drinking water induces a strong inflammatory response in the intestine. Mice lose as much as 10% of their initial body weight during the DSS cycles [16]. At week 12 after AOM/DSS treatment, we documented tumour development by endoscopy and histology (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Intratumoral Tregs are even more complex, since they have been reported to be associated with poor or favorable prognosis, not only in different cancer types, but also in the same cancer (94,95). It may reflect the heterogeneity of Treg subsets (96) in the tumor microenvironment or the selectivity of Treg markers (97).…”
Section: Other Parameters Impacting Cd8 + T Cells In Cancer Immunoedimentioning
confidence: 99%
“…Decline in CD4 + T effector cell function with progressive tumor growth in HCC is related to increased Treg mediated suppression [3,4]. Even though, the suppressive role of Tregs during the inflammation is beneficial for maintenance of normal immune homeostasis, increase in the number of Tregs during tumor progression suppresses CD8 + T effector cell mediated anti-tumor immunity; hence creating a barrier to successful immunotherapy of cancer [57]. On the contrary, a paradox has been reported in colorectal cancer; while some studies concluded that high density of Tregs in the tumor microenvironment is associated with better prognosis, other studies reported their elevated numbers are associated with advanced stage tumors and poor overall survival [8].…”
Section: Immunosuppression By Tregsmentioning
confidence: 99%